Psychological autopsies: religious and spiritual factors for suicide in cases and controls - Ali, Syeda Ayat-e-Zainab; Saleem, Tamkeen (Frontiers in Psychiatry, 2024)
In recent years, there has been a growing body of evidence supporting the notion that spirituality and religion can improve one's physical and mental health. Studies show that religion and spirituality play a significant role in the suicidal path. Considering the dearth of data on the patterns of suicidal thoughts, acts and related factors in Pakistan, a country with a large Muslim population and stigma with sociocultural perceptions of religious notions, the current study investigated the role of religious and spiritual factors of suicide using psychological autopsies. Purposive sampling was used to gather retrospective data records from police stations and hospital forensic departments in Rawalpindi and Islamabad, Pakistan, between January 2021 and July 2022. In total, 60 samples (30 cases and 30 controls) were used in this autopsies investigation. As with the majority of case control studies, the study sample cases were matched with the controls. At least two close bereaved family members served as the primary information sources, and data was gathered using the Semi Structured Interview Protocol for Psychological Autopsies. According to statistical analysis, both the suicide cases and the controls were comprised mostly of Muslim individuals. They follow Islam and hold the view that suicide is prohibited, forbidden, and haram in Islam. Regarding spirituality and religion, the majority of cases, according to the respondents interviewed, were not spiritual at all, while the controls are slightly spiritual. While the majority of both cases and controls had reduced interest in or practice of religious activities over the past year, a higher number of cases rarely performed and attended the religious services/activities as compared to controls. It was thus evident that the cases lacked significant engagement in spiritual and religious activities, and their attendance at such gatherings had notably decreased in the year preceding the suicide attempt. This decline in involvement in spiritual and religious practices might be linked to decreased levels of satisfaction, sense of belongingness, which could raise the risk of suicide. Therefore, in nations where Muslims predominate, culturally relevant suicide prevention initiatives including spiritual and religious treatments aimed at reducing the risk of suicide should be considered.